Covid-19 Pandemic Impact Study on Student Learning and Physical Activities in MAN Kota Blitar - Achmad Abdul Azis; Suroto Suroto; Gigih Siantoro (BIRCU, 2021)
The process of learning from home with the application of Distance Learning (PJJ) coupled with the existence of Social Restrictions by the government certainly makes changes in the daily patterns of students. Changes include learning activities and physical activity. The implementation of the new system has many obstacles that arise. Such constraints include the readiness of human resources including the readiness of teachers, students, and parental assistance as well as facilities and infrastructure, especially related to technology and information facilities and internet networks The same thing also happens when social restrictions. This causes many students' activities to be restricted so that students tend to be at homeless physical activity. This study was conducted to describe learning activities and physical activity during the Covid-19 pandemic. Assessment of learning activities using instruments designed by researchers and authorized by validators. While the assessment learning activity using questionnaires adopted from who is Global Physical Activity Questionnaire (GPAQ). Respondents were students of MAN Kota Blitar. Sampling Techniques with Simple Random Sampling. The stages of data analysis using descriptive analysis. Based on the results of the analysis, the data obtained is as follows: First, the condition of students' learning activities during the covid-19 pandemic is measured by the research instruments of learning activities showed the figure of 61.23% interpreted to be in the category of less good. Second, based on the results of the analysis, the condition of physical activity of students during the covid-19 pandemic was measured by GPAQ research instruments showing data on an average of 3670.77 MET. If we compare with the category table then we can mean that the average respondent has a high level of activity.